SURVEI INDEKS KEPUASAN KONSUMEN ATAS PELAYANAN RUMAH SAKIT UMUM DAERAH - Basuki, Agus Tri (Jurnal Ekonomi & Studi Pembangunan, 2011)
Abstract: This research aims to observe servicing government agencies in terms of this servicefrom Temanggung regency hospital to the patient. Service performance of governmentagencies measured using Public Satisfaction Index (IKM), based on the decision of the Ministerof State Apparatus, Number 25/Kep/m. Pan/2/2004, of the General guidelines in the preparation of community satisfaction index of the service unit of government agencies. Theresults of this research show that Public Satisfaction Index for the entire public service,installation emergency, inpatient and outpatient meets the criteria of 62,51 up to 81,25, so weconclude that public service in the Temanggung regency hospital is already good. Someimprovements to the service needed, is for the convenience of the services of the hospital (theinstallation of emergency room, polyclinics, outpatient and inpatient) is the lowest rank, followed by elements of the Justice and Accountability of officer. Abstrak: Penelitian ini bertujuan mengamati pelayanan instansi pemerintah dalam hal inipelayanan dari RSUD kabupaten Temanggung kepada pasien. Kinerja pelayanan instansipemerintah diukur dengan menggunakan Indeks Kepuasan Masyarakat (IKM) berdasarkanKeputusan Menteri Pendayagunaan Aparatur Negara Nomor Kep/25/M.Pan/2/ 2004 tentangPedoman Umum Penyusunan Indeks Kepuasan Masyarakat Unit Pelayanan InstansiPemerintah. Hasil penelitian ini menunjukkan bahwa Indeks Kepuasan Masyarakat untukseluruh layanan Poliklinik, Instalasi Gawat Darurat, Rawat Inap dan Rawat Jalan memenuhikriteria antara 62,51–81,25, sehingga dapat kita simpulkan bahwa pelayanan publik di RSUDkabupaten Temanggung adalah sudah baik. Beberapa perbaikan pelayanan yang diperlukan,yaitu: untuk kenyamanan pelayanan produk RSUD (IGD, Rawat Jalan, Poliklinik dan RawatInap) ada di ranking terendah, disusul unsur Keadilan dan Akuntabilitas petugas.